A preliminary analysis of the mining-induced rock movement characteristics in the Xinli deposit of the Sanshandao gold mine - Liu, Jia; Ma, Fengshan; Guo, Jie; Li, Guang; Song, Yewei; Li, Fangrui (Frontiers in Earth Science, 2023)
With the development of economic globalization, people's demand for mineral resources is also increasing. And with it comes the ground subsidence problem and rock movement problems. Many scholars have developed various ground subsidence prediction method, however, most methods are concentrated on flat coal seam mining which differs markedly from steeply inclined metal ore bodies. The related researches on steep dip metal ore bodies is very rare. In this paper, the Interferometric Synthetic Aperture Radar (InSAR) techniques, numerical simulation method and mathematical analysis are used to analyze the characteristics of rock movement in Xinli deposit of Sanshandao gold mine which is a steeply inclined coastal metal mine. Finally, we found that the small baseline subset (SBAS) technique show better applicability in coastal area than the persistent scatterer interferometry (PSI) technique, the southern part of the coastline within the Xinli Village area has greater subsidence value. The numerical simulation results obtained by the fast Lagrangian analysis of continua in 3 dimensions (FLAC3D) are also consistent with this result. In addition, the range of ground subsidence obtained by numerical simulation shows obvious asymmetry. The plausible explanation for this phenomenon can be drawn from the monitoring data of the No. 55 prospecting profile: the slope of the right part of the maximum subsidence point of the subsidence curve is smaller than that on the left part, i.e. the surrounding rock of fault hanging wall has a wider range of rock movements. Furthermore, the sublevels of the No. 55 prospecting profile at different depths show different rock movement characteristics, and the logistic function can be well applied to part of the settlement curve (the right part), the value of parameter “a” in the function formula is very close to the maximum subsidence value of each sublevel. We defined a ratio “r” to measure the difference between the maximum subsidence value and the corresponding parameter “a”, and found that this value is positively correlated with the fractal dimension value in deeper sublevels (−320 m, −400 m, −480 m, −600 m), and be negatively correlated with the fractal dimension value in lower sublevels (−200 m, −240 m).